Assessment of two-component backfill grouting quality for TBM tail voids via scaled physical modeling: Effects of injection flow rate, hardener dosage, and water-to-cement ratio - Hyun-Jun Kim; JunHyuk Jang; Daehui Kim; Tae-Hyuk Kwon; Tae-Young Kim; Song-Hun Chong; Min-Ji Kim; Tae-Min Oh; Hee-Hwan Ryu (Tunnelling and Underground Space Technology, 2026)

Upcycling battery scrap into commercial-grade graphite anode materials via coal tar-assisted granulation - Jongyun Choi; Tae Hun Kim; Gyujin Song; Sei-Min Park; Ji Chul Jung; Jung-Chul An; Inchan Yang (Chemical Engineering Journal, 2026)

Tailored medium-entropy Si alloy anodes with multi-element Fe-site substitution for high-performance Li-ion batteries - Byeong Guk Kim; Jung-Hyeok Park; Jihyeon Ryu; Kyungmin Do; Dong Gyun Hong; Tae-Hyun Kwon; Oh Sung Kwon; Insung Jang; Jaeik Hyun; Geon-Hyoung An; Youngoh Kim; Geon-Woong Lee; et al. (Chemical Engineering Journal, 2026)

Prediction of Seismic Earth Pressure on Basement Walls of Buildings with Rigid Base Conditions - Quang Thien Buu Nguyen; Tae-Hun Hwang; Sung-Ryul Kim (Bulletin of Earthquake Engineering, 2026)

Evaluation of electrostatic spray technology under varied particle characteristics and spray-solution compositions for particulate matter control - Yong-Hwan Oh; Seo Hee Seo; Sang-Hee Jo; Tae-Hun Kim; Youn-Suk Son (Journal of Environmental Chemical Engineering, 2026)

Age-related increase of NLRC4 inflammasome and TGF-β1 signaling exacerbates airway inflammation and remodeling in asthma - Jin-Hwa Kim; Hyun-Tae Kim; Jeong-Won Kim; Ji-Soo Jeong; Su-Ha Lee; Kwan-Hoo Kim; Na-Young Kim; Young-Hun Kim; Je-Won Ko; Tae-Won Kim (GeroScience, 2026)

Electron beam-induced decomposition of nitrous oxide (N2O) and the critical role of oxygen - Jieun Son; Sang-Hee Jo; Yong-Hwan Oh; Tae-Hun Kim; Tak-Hyun Kim; Seungho Yu (Journal of Environmental Management, 2026)

Exosomal microRNA profiling reveals candidate biomarkers and regulatory signatures associated with paratuberculosis disease status in goats - Eun-Yeong Bok; Tae Yoon Kim; Sang-Young Seo; Han-Gyu Lee; Young-Hun Jung; Seong Hwan Bae; Nam Su Oh; Tae Jin Cho; Hyeon Woo Park; Eui Cheol Shin; Jae Kyeom Kim (The Veterinary Journal, 2026)

Antiviral potential and mode of action of Metarhizium pinghaense 15R-derived polysaccharide against baculovirus - Jiwon Jang; Gui Hwan Han; Seong Hun Im; Jeong Won Kim; Soo Dong Woo; Tae Young Shin (Journal of Invertebrate Pathology, 2026)

Methane decomposition and characterization of conversion products in a continuous process via electron beam irradiation - Sang-Hee Jo; Jieun Son; Tae-Hun Kim; Tak-Hyun Kim; Seungho Yu (Process Safety and Environmental Protection, 2026)

Integrated MEA for polymer electrolyte membrane fuel cells enabled by freeze–casting and direct membrane deposition - Hyeon-Seung Jung; Seung Tae Lee; Seung-Hyeon Moon; Chanho Pak; Jae-Hun Kim (Chemical Engineering Journal, 2026)

Visualization of two-phase mass transport using a prism-embedded operando cell in membrane-electrode assembly-based electrochemical devices - Ok-Hee Kim; Hyuckjae Choi; Junho Kim; Jongwon Yang; Cheunho Chu; Hosung Choi; Hee Ji Choi; WooKeon Yang; Tae-Ho Kim; Yong-Hun Cho; Ilchai La; Yung-Eun Sung (Chemical Engineering Journal, 2025)

Comparative study of the stability of composite cathodes based on sulfide solid electrolytes for all-solid-state lithium-ion batteries - Jae-Ho Park; Jiwon Jeong; Daseul Han; Jun Tae Kim; Hun-Gi Jung; Woo Young Yoon; Kyung-Wan Nam; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Identification of candidate genes associated with resistance to Heterodera sojae in soybean - Heonil Kang; Jiyong Song; Hyoung-Rai Ko; Jae Eun Jo; Ji-Hun Hwang; Yeon-Ki Kim; Soo-Kwon Park; Gyu Tae Park; Tae-Hwan Jun; Bo-Keun Ha; Zenglu Li; Kyung Do Kim (Theoretical and Applied Genetics, 2025)

Analytical method for estimating dynamic earth pressure on basement walls considering building inertia and soil–structure interaction - Quang Thien Buu Nguyen; Byong-Youn Hwang; Tae-Hun Hwang; Sung-Ryul Kim (Soil Dynamics and Earthquake Engineering, 2025)

Optimization of an electrostatic spray system for control of particulate matter generated from electron beam flue gas treatment processes - Yong-Hwan Oh; Sang-Hee Jo; Jieun Son; Hui-Bom Jeong; Seo Hee Seo; Tae-Hun Kim; Youn-Suk Son (Process Safety and Environmental Protection, 2025)

The role of tight junctions in the pathogenesis of inflammatory bowel disease: immune modulation and barrier dysfunction - Ji Woong Heo; Min Jung Kim; Ye Jin Yang; Han Nim Choi; Kwang Youn Kim; Tae Woo Oh; Ju-Hye Yang; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Effect of soil-structure interaction on seismic earth pressure acting on building basements using 1g shaking table tests - Byong-Youn Hwang; Nghiem Xuan Tran; Tae-Hun Hwang; Seongho Hong; Quang Thien Buu Nguyen; Sung-Ryul Kim (Soil Dynamics and Earthquake Engineering, 2025)

Rational design strategy of co-self-assembled monolayers for high-efficiency and stable inverted perovskite solar cells - Haoran Zhou; Jung Jae Do; Young Hun Jung; Hoon Kang; Soyeon Kwon; Gyung Hyun Kim; Yekyung Kim; Tae Hoon Park; Eun Joong Kim; Chang Woo Byun; Jang Hyuk Kwon; Sungyeop Jung; et al. (Chemical Engineering Journal, 2025)

Innovative electrostatic spray technology for control of particulate matter emitted from electron beam flue gas treatment process - Yong-Hwan Oh; Sang-Hee Jo; Jieun Son; Hui-Bom Jeong; Seo Hee Seo; Tae-Hun Kim; Youn-Suk Son (Process Safety and Environmental Protection, 2025)

Efficient NOx and SO2 removal using NaOH additive in electron beam flue gas treatment process - Yong-Hwan Oh; Sang-Hee Jo; Jieun Son; Tak-Hyun Kim; Tae-Hun Kim; Youn-Suk Son (Journal of Environmental Chemical Engineering, 2025)

Highly activated phosphate-derived oxyhydroxide overlayer for enhancing photoelectrochemical ammonia oxidation-boosted hydrogen evolution - Phuong Thi Pham; Jong Hun Kim; Won Tae Hong; Hyungu Han; Seung Hun Roh; Xu Yu; Heeyeop Chae; Jongwook Park; Min-Cheol Kim; Chang Hyuck Choi; Jung Kyu Kim (Chemical Engineering Journal, 2025)

Symmetric and asymmetric non-fullerene acceptors cooperate synergistically for ternary optoelectronic devices - Minyoung Lim; Xiaoling Ma; Yelim Kang; Min Hun Jee; Soonyong Lee; Sang Young Jeong; Tae Hyuk Kim; Jae Won Shim; Fujun Zhang; Han Young Woo (Chemical Engineering Journal, 2025)

Effect of soil-building interaction on dynamic earth pressure on basement walls - Quang Thien Buu Nguyen; Byong-Youn Hwang; Tae-Hun Hwang; Sung-Ryul Kim (Soil Dynamics and Earthquake Engineering, 2024)

Removal of livestock odor gas ammonia, hydrogen sulfide, methanethiol by electron beam in a continuous flow system - Dong-Woo Kim; Sang-Hee Jo; Jieun Son; Seungho Yu; Tae-Hun Kim; Meehye Lee; Tak-Hyun Kim (Journal of Environmental Chemical Engineering, 2024)

Enhanced oxidation of parabens in an aqueous solution by air-assisted cold plasma - Hee-Jun Kim; Tae-Hun Lee; Youngpyo Hong; Jae-Cheol Lee; Hyun-Woo Kim (Chemosphere, 2024)

Exploring green solvents for the sustainable fabrication of bio-based polylactic acid membranes using nonsolvent-induced phase separation - Tunmise Ayode Otitoju; Chang-Hun Kim; Mihee Ryu; Jaesung Park; Tae-Kyung Kim; Youngmin Yoo; Hosik Park; Jung-Hyun Lee; Young Hoon Cho (Journal of Cleaner Production, 2024)

Association between sickness presenteeism and depressive symptoms: a cross-sectional study using the 6th Korean working conditions survey - Myeong-Hun Lim; Min-Seok Kim; Seong-Uk Baek; Tae-Yeon Kim; Jong-Uk Won; Jin-Ha Yoon (International Archives of Occupational and Environmental Health, 2024)

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

Adsorption effects of electron scavengers and inorganic ions on catalysts for catalytic oxidation of sulfamethoxazole in radiation treatment - Kang Lee; Tae-Hun Kim; Sang-Hee Jo; Seungho Yu (Chemosphere, 2024)

Ultrasound-assisted sustainable recycling of valuable metals from spent Li-ion batteries via optimisation using response surface methodology - Theoneste Nshizirungu; Masud Rana; Young Tae Jo; Eugenie Uwiragiye; Jaepil Kim; Jeong-Hun Park (Journal of Environmental Chemical Engineering, 2024)

Pharmacological effects of pentacyclic triterpenoids isolated from Centella asiatica - Dong-Hyun Min; Young-Beom Yu; Tae-Hun Kim; Hoon Kim; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2024)
Centella asiatica (CA) is one of the most popular traditional herbal medicines worldwide. It has been used for centuries in many countries, especially for curing skin damage, and is now applied to treat various human diseases. There are various types of triterpenoids from Centella asiatica , with four pentacyclic triterpenoids with the main properties being shown by four pentacyclic triterpenoids: asiaticoside, madecassoside, asiatic acid, and madecassic acid. These terpenoids have similar structures, however each has a slightly different properties. Asiaticoside, madecassoside, asiatic acid, and madecassic acid are synthesized through the isoprenoid pathway known as mevalonate pathway to produce hydrophobic triterpenoid structures (aglycone) which contain hydrophilic sugar chains (glycone). Furthermore, asiaticoside and madecassoside are distinguished by a glycone, and asiatic acid and madecassic acid are distinguished by a aglycone. These pentacyclic triterpenoids have a wide spectrum of beneficial effects and have been used as anti-inflammatories, skin wound treatments, scar treatments, and cosmetics agents. This review aimed to provide a description of the four compounds, of their structure, pharmacological properties, applications in the treatment of various diseases, known mechanisms of action, and commentary on industrial applications.

Degradation of micropollutants by gamma irradiation: Insight of transformation product formation explored by suspect and non-target screening using LC-HRMS - Heewon Jang; Tae-Hun Kim; Junho Jeon (Journal of Environmental Chemical Engineering, 2024)

Correction: Improvement and Analysis for Accuracy of Baseflow Using SWAT-CUP Premium in the Yongjeon Stream, South Korea - Jong-Tae Kim; Chang-Hun Lee; Namjoo Lee (Pure and Applied Geophysics, 2024)

Improvement and Analysis for Accuracy of Baseflow Using SWAT-CUP Premium in the Yongjeon Stream, South Korea - Jong-Tae Kim; Chang-Hun Lee; Namjoo Lee (Pure and Applied Geophysics, 2024)
Here, the results of Soil and Water Assessment Tool (SWAT) simulation are calibrated and validated using SWAT-CUP Premium, and the R 2 (coefficient of determination) values of simulated and observed flows are compared. According to the SWAT analysis of the Cheongsong Yongjeon stream basin, low accuracy of 0.40 was the R 2 value for simulated and observed flows, and the baseflow was calculated at an annual average of 46.659 m 3 /s. During the same period, after calibration and validation using SWAT-CUP Premium, the R 2 value of simulated and observed flows was improved to 0.71, and the evaluation indexes showed 0.51 for Nash–Sutcliffe efficiency (NS), 37.1 for percent bias (PBIAS), 0.73 for P-factor, and 0.33 for R-factor, indicating that the relationship between observed and simulated flows was improved. In addition, after calibration and validation, the baseflow was 56.951 m 3 /s, which was a more accurate value than the one before calibration and validation.

Micro-grinding–based production for sulforaphene-enriched radish seeds extract via facilitating glucosinolates-myrosinase reaction, and evaluation of its anti-adipogenic effects - Tae Kyung Lee; Gihyun Hur; Jong Hun Kim; Jung Han Yoon Park; Hee Yang; Ki Won Lee (Food Chemistry, 2023)

Antioxidant-Coated multifunctional whitlockite scaffold for the treatment of Steroid-Induced osteonecrosis of the femoral head - Jung Hun Kim; QuanZhe Liu; Uk-Jae Lee; Arun Kumar Rajendran; MinJoon Cho; Sivashanmugam Amirthalingam; Tae Hoon Kang; Beom Seok Kim; Gyeong-Guk Park; Byung-Gee Kim; Jae Hyup Lee; Nathaniel S. Hwang (Chemical Engineering Journal, 2023)

Internal carbon loop strategy for methanol production from natural gas: Multi-objective optimization and process evaluation - Sung-Jong Jo; Tae-Ha Kang; Beom-Ju Shin; Ji-Hun Mun; Sijan Devkota; Jin-Young Cha; Shaukat Ali Mazari; Kyung-Min Kim; Ung Lee; Chae-Ho Shin; Jong-Ho Moon (Journal of Cleaner Production, 2023)

Macroalgae as a source of sugar and detoxifier biochar for polyhydroxyalkanoates production by Halomonas sp. YLGW01 under the unsterile condition - Shashi Kant Bhatia; Jeong Hyeon Hwang; Suk Jin Oh; Hyun Jin Kim; Nara Shin; Tae-Rim Choi; Hyun-Joong Kim; Jong-Min Jeon; Jeong-Jun Yoon; Yung-Hun Yang (Bioresource Technology, 2023)

Investigating the effect of blending of diamine and alkanolamine for CO2 capture: Experiment and thermodynamic modeling of CO2-AEEA-DEA-H2O system - Shaukat Ali Mazari; Tae-Ha Kang; Sijan Devkota; Jin-Young Cha; Beom-Ju Shin; Ji-Hun Mun; Kyung-Min Kim; Ung Lee; Jong-Ho Moon (Chemical Engineering Journal, 2023)

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

True self-reinforced composites enabled by tuning of molecular structure for lightweight structural materials in future mobility - Hyeseong Lee; Ji-un Jang; Jaewoo Kim; Yoon Sang Kim; Jaehyun Cho; Mi Na Kim; Jung Tae Lee; Woo Hyuk Choi; Jong Man Song; Won June Song; Dong Hui Won; Deok Woo Yun; et al. (Chemical Engineering Journal, 2023)

Cutting-edge technological advancements in biomass-derived hydrogen production - Shouvik Saha; Amita Mondal; Mayur B. Kurade; Yongtae Ahn; Priyabrata Banerjee; Hyun-Kyung Park; Ashok Pandey; Tae Hyun Kim; Byong-Hun Jeon (Reviews in Environmental Science and Bio/Technology, 2023)

Algal biochar mediated detoxification of plant biomass hydrolysate: Mechanism study and valorization into polyhydroxyalkanoates - Shashi Kant Bhatia; Ranjit Gurav; Do-Hyun Cho; Byungchan Kim; Hee Ju Jung; Su Hyun Kim; Tae-Rim Choi; Hyun-Joong Kim; Yung-Hun Yang (Bioresource Technology, 2023)

Advances in physicochemical pretreatment strategies for lignocellulose biomass and their effectiveness in bioconversion for biofuel production - Bikram Basak; Ramesh Kumar; A.V.S.L. Sai Bharadwaj; Tae Hyun Kim; Jung Rae Kim; Min Jang; Sang-Eun Oh; Hyun-Seog Roh; Byong-Hun Jeon (Bioresource Technology, 2023)

Protective effect of 7-hydroxyl-1-methylindole-3-acetonitrile on the intestinal mucosal damage response to inflammation in mice with DSS-induced colitis - Kyung-Sook Chung; Sang-Eun Park; Jung-Hun Lee; Su-Yeon Kim; Hee-Soo Han; Yong Sup Lee; Seang-Hwan Jung; Eungyeong Jang; Sangmin Lee; Kyung-Tae Lee (Chemico-Biological Interactions, 2023)

Review of chemical pretreatment of lignocellulosic biomass using low-liquid and low-chemical catalysts for effective bioconversion - A.V.S.L Sai Bharadwaj; Subhabrata Dev; Jingshun Zhuang; Yunxuan Wang; Chang Geun Yoo; Byong-Hun Jeon; Srijan Aggarwal; Seung Hyun Park; Tae Hyun Kim (Bioresource Technology, 2023)

Exposure assessment for pesticide residues in agricultural products consumed in the Republic of Korea during 2016–2020 - Tae-Hun Kim; Su Chin Park; Ji Eun Kim; Hyun Jun Yeon; Ju Ho Kim; Young Soek Park; Soo-Hwaun Kim; Yoon-Hee Oh; Gune-Hee Jo (Environmental Science and Pollution Research, 2023)

Overexpression of the ginseng GH18 gene confers salinity tolerance in Arabidopsis - Gayoung Noh; Ji-Hyun Kim; Sung Won Cho; Young-Hun Kim; Ju-Young Jung; Woo-Jong Hong; Ki-Hong Jung; Gyulim Park; Hong-Joo Son; Ick Hyun Jo; Young Hun Song; Sun Tae Kim; et al. (Plant Biotechnology Reports, 2022)

Biotransformation of C20- and C22-polyunsaturated fatty acids to 11S- and 13S-hydroxy fatty acids by Escherichia coli expressing 11S-lipoxygenase from Enhygromyxa salina - Jin Lee; Tae-Hun Kim; Kyung-Chul Shin; Tae-Eui Lee; Min-Ju Kim; Deok-Kun Oh (Biotechnology Letters, 2022)

Universal Stress Protein (USP) Enhances Plant Growth and Development by Promoting Cell Expansion - Eun Seon Lee; Kieu Anh Thi Phan; Sang Eun Jun; Joung Hun Park; Seol Ki Paeng; Ho Byoung Chae; Seong Dong Wi; Su Bin Bae; Kee Ryeon Kang; Gyung-Tae Kim; Sang Yeol Lee (Journal of Plant Biology, 2022)

Bone Generation Following Repeated Administration of Recombinant Bone Morphogenetic Protein 2 - Hye-Ju Son; Mi Nam Lee; Yuri Kim; Hyuck Choi; Byung-Chul Jeong; Sin-Hye Oh; Jung-Woo Kim; Seung-Hee Kwon; Sun-Hun Kim; Soo-Chang Song; Shee Eun Lee; Jeong-Tae Koh (Tissue Engineering and Regenerative Medicine, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Dual role of reactive oxygen species in autophagy and apoptosis induced by compound PN in prostate cancer cells - Hyeun Deok Choi; Kwang-Youn Kim; Kwang Il Park; Sang-Hun Kim; Sul-Gi Park; Sun-Nyoung Yu; Young-Woo Kim; Dong Seob Kim; Kyung Tae Chung; Soon-Cheol Ahn (Molecular & Cellular Toxicology, 2021)

Exposure assessment and safe intake guidelines for heavy metals in consumed fishery products in the Republic of Korea - Tae-Hun Kim; Ju Ho Kim; Min Dil Le Kim; Won Duck Suh; Ji Eun Kim; Hyun Jun Yeon; Young Soek Park; Soo-Hwaun Kim; Yoon-Hee Oh; Gune-Hee Jo (Environmental Science and Pollution Research, 2020)

Anti-inflammatory effect of bee venom in phthalic anhydride-induced atopic dermatitis animal model - Yu Jin Lee; Myung Jin Oh; Dong Hun Lee; Yong Sun Lee; Jiin Lee; Deok-Hyun Kim; Cheol-Hoon Choi; Min Jong Song; Ho Sueb Song; Jin Tae Hong (Inflammopharmacology, 2020)

Synthesis and anti-endoplasmic reticulum stress activity of N-substituted-2-arylcarbonylhydrazinecarbothioamides - Hoon Choi; Wheesahng Yun; Jung-hun Lee; Seoul Jang; Sang Won Park; Dong Hwan Kim; Kyoung Pyo Seon; Jung-mi Hyun; Kwiwan Jeong; Jin-mo Ku; Tae-gyu Nam (Medicinal Chemistry Research, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Calibration of the Pyranometer Sensitivity Using the Integrating Sphere - Bu-Yo Kim; Kyu-Tae Lee; Il-Sung Zo; Sang-Ho Lee; Hyun-Seok Jung; Se-Hun Rim; Jeong-Pil Jang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Correction to: Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

A Scalable High-Performance I/O System for a Numerical Weather Forecast Model on the Cubed-Sphere Grid - Junghan Kim; Young Cheol Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Retrieval Algorithm for Broadband Albedo at the Top of the Atmosphere - Sang-Ho Lee; Kyu-Tae Lee; Bu-Yo Kim; ll-Sung Zo; Hyun-Seok Jung; Se-Hun Rim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Heavy metal stabilization in contaminated soil by treatment with calcined cockle shell - Mohammad Nazrul Islam; Golam Taki; Xuan Phuc Nguyen; Young-Tae Jo; Jun Kim; Jeong-Hun Park (Environmental Science and Pollution Research, 2017)

Human chorionic gonadotropin (hCG) sub-chronic administration mediated MMP-9 activities and cytokine association deteriorate experimental autoimmune encephalomyelitis (EAE) condition in mice model - Joon-Seung Han; Khandoker Asiqur Rahaman; Ji-Eun Seo; Mahbub Hasan; Kyung-Tae Lee; Hophil Min; Kang Mi Lee; Ju-Hyung Park; Ho Jun Kim; Ki Hun Kim; Junghyun Son; Jaeick Lee; et al. (Journal of Pharmaceutical Investigation, 2016)

Geophysical evidence and inferred triggering factors of submarine landslides on the western continental margin of the Ulleung Basin, East Sea - Deniz Cukur; Seong-Pil Kim; Gee-Soo Kong; Jang-Jun Bahk; Senay Horozal; In-Kwon Um; Gwang-Soo Lee; Tae-Soo Chang; Hun-Jun Ha; David Völker; Jung-Ki Kim (Geo-Marine Letters, 2016)

Genomic structure, expression and association study of the porcine FSD2 - Kyu-Sang Lim; Kyung-Tai Lee; Si-Woo Lee; Han-Ha Chai; Gulwon Jang; Ki-Chang Hong; Tae-Hun Kim (Molecular Biology Reports, 2016)

Mitochondria-targeted DsRed2 protein expression during the early stage of bovine somatic cell nuclear transfer embryo development - Hyo-Jin Park; Sung-Hun Min; Hoonsung Choi; Junghyung Park; Sun-Uk Kim; Seunghoon Lee; Sang-Rae Lee; Il-Keun Kong; Kyu-Tae Chang; Deog-Bon Koo; Dong-Seok Lee (In Vitro Cellular & Developmental Biology - Animal, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Development of liquid chromatography tandem mass spectrometry method for determination of spironolactone in human plasma: application to a bioequivalence study of Daewon Spiracton tablet® (spironolactone 50 mg) - Jeong-Hun Lee; Tae-Gil An; Su Jung Kim; Wang-Seob Shim; Kyung-Tae Lee (Journal of Pharmaceutical Investigation, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Distribution and long-term trends in various fog types over South Korea - Miloslav Belorid; Chong Bum Lee; Jea-Chul Kim; Tae-Hun Cheon (Theoretical and Applied Climatology, 2015)

Removal of Iopromide and Its Intermediates from Ozone-Treated Water Using Granular Activated Carbon - Yong-Tae Ahn; Dong-Wan Cho; Akhil N. Kabra; Min-Kyu Ji; Yeojoon Yoon; Jaewon Choi; Il-Hwan Choi; Joon-Wun Kang; Jung Rae Kim; Byong-Hun Jeon (Water, Air, & Soil Pollution, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Polymorphism analysis of tyrosine hydroxylase gene variable number of tandem repeats in various Korean dogs - Hee-Eun Lee; Bong-Hwan Choi; Dong-Hoon Lee; Yun-Jeong Kwon; Jungwoo Eo; Yuri Choi; Hoim Jeong; Jeong-An Gim; Tae-Hun Kim; Ji-Hong Ha; Kook-Il Han; Heui-Soo Kim (Genes & Genomics, 2015)

Statistical analysis and genetic diversity of three dog breeds using simple sequence repeats - Hoim Jeong; Bong-Hwan Choi; Jungwoo Eo; Yun-Jeong Kwon; Hee-Eun Lee; Yuri Choi; Jeong-An Gim; Tae-Hun Kim; Hwan-Hoo Seong; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; et al. (Genes & Genomics, 2014)

Genetic structure and variability of the working dog inferred from microsatellite marker analysis - Yun-Jeong Kwon; Bong-Hwan Choi; Jungwoo Eo; Choongrak Kim; Yi-Deun Jung; Ja-Rang Lee; Yuri Choi; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Dae-Soo Kim; Jae-Won Huh; et al. (Genes & Genomics, 2014)

Polymorphism analysis of tyrosine hydroxylase (TH) in military working dogs - Jungwoo Eo; Bong-Hwan Choi; Yi-Deun Jung; Yun-Jeong Kwon; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2013)

Porcine insulin-like growth factor 1 (IGF1) gene polymorphisms are associated with body size variation - Pengxia Niu; Sang-Wook Kim; Bong-Hwan Choi; Tae-Hun Kim; Jong-Joo Kim; Kwan-Suk Kim (Genes & Genomics, 2013)

Genome-wide copy number variation in Hanwoo, Black Angus, and Holstein cattle - Jung-Woo Choi; Kyung-Tai Lee; Xiaoping Liao; Paul Stothard; Hyeon-Seung An; Sungmin Ahn; Seunghwan Lee; Sung-Yeoun Lee; Stephen S. Moore; Tae-Hun Kim (Mammalian Genome, 2013)

mRNA sequence analysis and quantitative expression of the ADAMTS4 gene in the thoroughbred horse - Jae-Woo Moon; Kung Ahn; Jin-Han Bae; Gyu-Hwi Nam; Byung-Wook Cho; Kyung-Do Park; Hak-Kyo Lee; Young-Mok Yang; Tae-Hun Kim; Hwan-Hoo Seong; Kyudong Han; Heui-Soo Kim (Genes & Genomics, 2012)

Identification and characterization of transposable element-mediated chimeric transcripts from porcine Refseq and EST databases - Hong-Seok Ha; Jae-Woo Moon; Jeong-An Gim; Yi-Deun Jung; Kung Ahn; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

In vitro CpG methylation and garcinol reduce PERV LTR promoter activity - Hong-Seok Ha; Young-Choon Lee; Sang-Je Park; Yi-Deun Jung; Kung Ahn; Jae-Woo Moon; Kyudong Han; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

Cryptonemia rotunda (Halymeniales) and Schizymenia apoda (Nemastomatales), two new records of red algae from Korea - Su-Yeon Kim; Tae-Ho Seo; Jeong-Kwang Park; Ga-Hun Boo; Kyeong-Mi Kim; Sung-Min Boo (Algae, 2012)

Novel PPARγ partial agonists with weak activity and no cytotoxicity; identified by a simple PPARγ ligand screening system - Min-Chul Cho; Dong-Hun Lee; Eun Jin Kim; Jee-young Lee; Jeong-Woo Kang; Jong Hwan Song; Youhoon Chong; Yangmi Kim; Jin-Tae Hong; Do-Young Yoon (Molecular and Cellular Biochemistry, 2011)

Detection of human parechoviruses in children with gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2011)

Treadmill exercise suppresses muscle cell apoptosis by increasing nerve growth factor levels and stimulating p-phosphatidylinositol 3-kinase activation in the soleus of diabetic rats - Chang-Hun Chae; Sung-Lim Jung; Sang-Hyun An; Chan-Kyoung Jung; Sang-Nam Nam; Hyun-Tae Kim (Journal of Physiology and Biochemistry, 2011)

Emergence of norovirus GII-4/2008 variant and recombinant strains in Seoul, Korea - Tae-Hee Han; Cheol-Hwan Kim; Ju-Young Chung; Sang-Hun Park; Eung-Soo Hwang (Archives of Virology, 2011)

Investigation of porcine FABP3 and LEPR gene polymorphisms and mRNA expression for variation in intramuscular fat content - Xiaoping Li; Sang-Wook Kim; Jung-Suck Choi; Yoon-Mi Lee; Cheol-Koo Lee; Bong-Hwan Choi; Tae-Hun Kim; Yang-Il Choi; Jong-Joo Kim; Kwan-Suk Kim (Molecular Biology Reports, 2010)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)

Genetic characterization of rotavirus in children in South Korea from 2007 to 2009 - Tae-Hee Han; Cheol-Hwan Kim; Ju-Young Chung; Sang-Hun Park; Eung-Soo Hwang (Archives of Virology, 2010)

Regulation of bone formation using rapamycin-induced BMP2 expression system: influence of implanted cell number - Dong-Jin Lim; Bae Keun Park; Won Gu Jang; Kkot-Nim Lee; Renny Franceschi; Sun-Hun Kim; Shee-Eun Lee; Jeong-Tae Koh (Molecular & Cellular Toxicology, 2010)

Detection of Human Bocavirus-2 in children with acute Gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; En-Jung Kim; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2009)

Detection of low-abundant novel transcripts in mouse hematopoietic stem cells - Hyeng-Soo Kim; Junmo Hwang; Young-Hun Kim; Seonggon Kim; Jae-Woong Lee; Hyung-Sik Kang; Kil Soo Kim; Ji-Hong Ha; Jin Woong Chung; Kyu-Tae Chang; Zae Young Ryoo; Sanggyu Lee (Molecular Genetics and Genomics, 2009)

Kinetic and regulatory properties of plant ADP-glucose pyrophosphorylase genetically modified by heterologous expression of potato upreg mutants in vitro and in vivo - Si-Myung Lee; Tae-Hun Ryu; Su-Il Kim; Thomas Okita; Donghern Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Overexpression of OgPAE1 from wild rice confers fungal resistance against Botrytis cinerea - Eun Hee Jeon; Eun Sook Chung; Jung Hun Pak; Jae Sung Nam; Sung Ki Cho; Sang Hyun Shin; Doh Hoon Kim; Gyung Tae Kim; Jai Heon Lee; Kyung Ho Kang; Young Soo Chung (Journal of Plant Research, 2008)

Analysis of metabolite profile data using batch-learning self-organizing maps - Jae Kwang Kim; Myoung Rae Cho; Hyung Jin Baek; Tae Hun Ryu; Chang Yeon Yu; Myong Jo Kim; Eiichiro Fukusaki; Akio Kobayashi (Journal of Plant Biology, 2007)

Proapoptotic activity of NAG-1 is cell type specific and not related to COX-2 expression - Tae Jung Jang; Nam II Kim; Chang Hun Lee (Apoptosis, 2006)

Antiviral Effects of Sulfated Exopolysaccharide from the Marine Microalga Gyrodinium impudicum Strain KG03 - Joung Han Yim; Sung Jin Kim; Se Hun Ahn; Chong Kyo Lee; Ki Tae Rhie; Hong Kum Lee (Marine Biotechnology, 2004)